Evaluating Islamic Religious Education Programs Through the Cronbach Decision-Oriented Model: Implications for Instructional Effectiveness - Siti Nur Hasanah; Sofiatil Aliyah; Moh. Sahlan; Mundir; Sofyan Hadi (AL-ADABIYAH: Jurnal Pendidikan Agama Islam, 2026)
This study aims to evaluate the effectiveness of Islamic Religious Education programs through the Cronbach decision-oriented evaluation model and to examine how evaluation findings contribute to instructional improvement and educational decision-making. The study was conducted at SMA Negeri 1 Kencong and SMA Negeri 2 Jember using a qualitative multi-site evaluative research design. Data were collected through observations, semi-structured interviews, and documentation analysis involving school principals, Islamic Religious Education teachers, curriculum coordinators, and students. Data analysis employed the interactive model of Miles, Huberman, and Saldaña, including data reduction, data display, conclusion drawing, and cross-site analysis. The findings indicate that Islamic Religious Education programs in both schools were generally implemented systematically through structured instructional planning, religious culture development, and classroom-based evaluation practices. However, evaluation systems remained predominantly focused on cognitive assessment and administrative reporting, while affective, spiritual, and behavioral dimensions were not yet evaluated comprehensively. The study further found that institutional culture, reflective learning interaction, and the integration of evaluation findings into instructional supervision significantly influenced instructional effectiveness and students’ moral-spiritual development. Moreover, the utilization of evaluation findings for sustainable educational decision-making and long-term program improvement remained relatively limited. The novelty of this study lies in the application of the Cronbach decision-oriented evaluation model within Islamic Religious Education using a qualitative multi-site approach integrating input, process, output, and outcome dimensions comprehensively. This study contributes theoretically to the development of Islamic educational evaluation studies and practically provides recommendations for strengthening holistic, reflective, and evidence-based evaluation systems within contemporary Islamic education.